Nonlinear dynamic analysis of pile foundation using finite element method - Goshu, Tewodros; Assefa, Eleyas; Jilo, Nagessa Zerihun; Assefa, S M; Pantelidis, Lysandros; Sachpazis, Costas; Mohammed, Hirei (My University, 2025)
Nonlinear dynamic response analysis of pile foundations is essential in seismic regions, where soil-pile-structure interaction governs safety and serviceability. Ethiopia's location along the African and Arabian tectonic plates exposes its infrastructure to high seismic risk, demanding rigorous foundation evaluation. This study investigates the pile foundations of Bridge B-40, part of the Awash-Kombolcha-Hara Gebeya railway project in the seismically active Afar Triangle (PGA = 0.3 g). Using PLAXIS 3D, with the Hardening Soil model at small strains and the Hoek-Brown model for rock, site-specific geotechnical and seismic data were incorporated to simulate static and dynamic conditions. Static analysis showed negligible settlement (0.55 mm), with stresses far below capacity. Free-field site response and free-vibration analyses established natural frequencies and captured seismic amplification effects. Under dynamic loading, ground accelerations varied between 24 and 136 cm/s2, and pile head displacement reached 91.24 mm, within structural limits. However, the maximum immediate settlement of 95.81 mm exceeded Eurocode serviceability criteria, signaling performance concerns despite adequate stability. Differential settlements between pile caps remained low (3.5-4.95 mm), and vertical stresses did not approach failure. These findings highlight the importance of nonlinear soil behavior in pile foundation design.
Keywords: Finite element analysis; Nonlinear dynamic analysis; Pile foundation; Seismic response